Implicações da ecologia acústica sobre processos de formação docente - Fuchs, Igor Hardok (2022)
This dissertation presents a narrative research carried out with students of Music from Universidade Federal de Santa Maria (UFSM), it studies the possible relations between Acoustic Ecology and the training of musical educators,. Acoustic Ecology studies the relationship between beings and their society mediated through sound, the effects of the soundscape. The works of the Canadian composer and musical educator Murray Schafer brought attention to the role of sound, questioning what musical education could do about any of the world´s environmental problems and the quality of the global soundscape. Schafer on A Sound Education brings many exercises to practice active listening. Among those exercises we find Sound Diaries, which brings acoustic ecology close to narrative research, in this case with the narrative of a soundscape. On this research we proposed 15 meetings containing expositions and discussions about acoustic ecology, The participants wrote sound diaries and composed sound art, that being part of the meetings and the research. We identified that the knowledge acquired as in the graduation course, and also, past life experiences come together with the new knowledges of Acoustic Ecology, creating new meanings for everyday life, and creating a new environmental conscience and a listening conscience, having an effect on their path as a music teacher.